Pengaruh Komunikasi. Komitmen Dan Struktur Organisasi Terhadap Kinerja Pengurus Organisasi Mahasiswa’’ ( Studi Kasus Pada Ikatan Mahasiswa Alumni Salafiyah Syafi’iyah Malang Raya) - Zeinorrida, Zeinorrida; Khalikussabir, Khalikussabir; Slamet, Afi Rachmat (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to analyze the influence of communication, commitment, and organizational structure on the performance of student organization members, with a case study on the Ikatan Mahasiswa Alumni Salafiyah Syafi’iyah (IKMASS) Malang Raya. The research uses a quantitative approach with an explanatory research design. Data were collected through questionnaires distributed to 56 respondents selected using purposive sampling from a total population of 56 active IKMASS members. The data were analyzed using instrument tests, classical assumption tests, and hypothesis testing. The results show that simultaneously, communication, commitment, and organizational structure influence member performance. However, partially, only the communication variable has a positive and significant effect on performance. Meanwhile, commitment and organizational structure do not show a significant influence. These findings highlight the importance of effective communication in enhancing the performance of student organization members. Keywords: Communication, Commitment, Organizational Structure, Performance